2020
DOI: 10.1371/journal.pone.0242817
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and viral suppression in HIV-positive Kenyan female sex workers on antiretroviral therapy

Abstract: Background Excessive alcohol intake has been associated with poor adherence to antiretroviral therapy (ART). The impact of alcohol on viral suppression is particularly important among groups at high risk of HIV transmission, such as female sex workers (FSWs). Few studies have directly evaluated the association between alcohol use and HIV viral load. We hypothesized that hazardous or harmful alcohol use is associated with detectable plasma viral load among HIV-positive FSWs. Methods A prospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
3
6
0
Order By: Relevance
“…1) For viral load suppression this study ndings are consistent with a study done in Kenya which showed that alcohol use was not associated with a suppressed viral load (15). Another study found that women aged 50 years and above were less likely to have a non-suppressed viral load than women under 50 years (33).…”
Section: Discussionsupporting
confidence: 88%
“…1) For viral load suppression this study ndings are consistent with a study done in Kenya which showed that alcohol use was not associated with a suppressed viral load (15). Another study found that women aged 50 years and above were less likely to have a non-suppressed viral load than women under 50 years (33).…”
Section: Discussionsupporting
confidence: 88%
“…The results were inconsistent with the findings in a study in Nepal where a low percentage of participants had hazardous alcohol use, dependence symptoms and harmful alcohol use 35 . A study done in Kenya on a different cohort from a different County found low percentages of hazardous alcohol use, dependence use and harmful use 36 .…”
Section: Discussionmentioning
confidence: 96%
“…35 Although the increase in substance use was not related to a greater likelihood of COVID-19 impact on HIV care, evidence suggests that substance use is, in general, related to poor HIV outcomes among FSW living with HIV. 36,37…”
Section: Discussionmentioning
confidence: 99%